2022
DOI: 10.3390/coatings12040476
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coatings by Natural and Synthetic Agents for Insect Control and Their Applications

Abstract: Insect repellent textiles offer protection against disease-causing vectors such as mosquitoes, flies, and ticks. Protection is based on the incorporation of insect repellent compounds present in plant oil derivatives or synthetic oils. The effectiveness and application of natural insect repellents such as citronella grass, lemongrass, rosemary, peppermint, holy basil, tea tree, neem, lavender, thyme, lemon eucalyptus, clove, and cinnamon oils, as well as synthetic compounds permethrin, allethrin, malathion, DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Also, clove oil was demonstrated to be effective in the attraction of other related tephritids [89]. However, contrarily, clove oil has also an important property as a biopesticide [90][91][92]. As a result, in this study, a variety of fractions were obtained, which, in the case of the distillation of the DCO, turned out to have a content in α-copaene between 1.64 to 2.85-fold more concentrated than the original oil (i.e., corresponding to the first three fractions); and, in the case of fractions corresponding to the distillation of IF between 1.62 to 2.11-fold (i.e., corresponding to the first two fractions).…”
Section: Discussionmentioning
confidence: 99%
“…Also, clove oil was demonstrated to be effective in the attraction of other related tephritids [89]. However, contrarily, clove oil has also an important property as a biopesticide [90][91][92]. As a result, in this study, a variety of fractions were obtained, which, in the case of the distillation of the DCO, turned out to have a content in α-copaene between 1.64 to 2.85-fold more concentrated than the original oil (i.e., corresponding to the first three fractions); and, in the case of fractions corresponding to the distillation of IF between 1.62 to 2.11-fold (i.e., corresponding to the first two fractions).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these compounds are classified as lipophilic monoterpenoid compounds with high volatility. This allows the compounds to penetrate the insect's skin more quickly so that in the end it can affect the physiological function (disrupts the metabolism of the insect and deters feeding) of insects [33,34].…”
Section: Effect Of Eucalyptus On the Survival Rate Of Insect Applied ...mentioning
confidence: 99%
“…There are several possibilities regarding the factors that support this occurrence, including its volatile nature and the presence of a repellent effect on E. citriodora. As one of the substantial components of E. citriodora, citronella is known to have fast evaporation and repellent properties [34]. Several studies have shown E. citriodora to have a repellent effect against some insects such as Zabrotes subfasciatus [35], S. zeamais [36], and Prostephanus truncatus [37].…”
Section: Effect Of Eucalyptus On the Survival Rate Of Insect Applied ...mentioning
confidence: 99%
“…Natural essential oils have received attention as potential candidates for tick control, due to their bioactive properties and relatively low environmental impact. These oils contain active compounds such as eugenol, cineole, linalool, and menthol, which have demonstrated insecticidal and repellent properties against various ticks, mosquitoes, and flies [ 4 ]. While previous research has explored the efficacy of individual essential oils against ticks, comparative analyses are still required to determine which oil offers the most effective and practical tick control solution.…”
Section: Introductionmentioning
confidence: 99%